2001
DOI: 10.1093/ajcn/74.6.747
|View full text |Cite
|
Sign up to set email alerts
|

Daily requirement for and splanchnic uptake of leucine in healthy adult Indians

Abstract: A tentative mean leucine requirement of 40 mg x kg(-1) x d(-1) is proposed for healthy Indian adults, as it is for Western subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…In general, the technical problems of precursor pool identification that are related to the DAAO/DAAB method are not present, since the indicator chosen is one in which the precursor pool is known and/or validated. This method is either applied as a short term IAAO method ( 15 ) or a longer-term 24 h IAAO and IAAB method ( 12 ) . The requirement is taken as the intake of amino acid that provides for an inflection (or breakpoint) in the pattern of the indicator amino acid oxidation or balance response to different test amino acid intakes.…”
Section: Amino Acid Requirements Based On Isotopic Techniquesmentioning
confidence: 99%
“…In general, the technical problems of precursor pool identification that are related to the DAAO/DAAB method are not present, since the indicator chosen is one in which the precursor pool is known and/or validated. This method is either applied as a short term IAAO method ( 15 ) or a longer-term 24 h IAAO and IAAB method ( 12 ) . The requirement is taken as the intake of amino acid that provides for an inflection (or breakpoint) in the pattern of the indicator amino acid oxidation or balance response to different test amino acid intakes.…”
Section: Amino Acid Requirements Based On Isotopic Techniquesmentioning
confidence: 99%
“…Although the recommended leucine intake is currently 14 mg$kg 21 $d 21 (66), the amount required to maximize the stimulation of muscle anabolic intracellular signaling may be at least 40-65 mg$kg 21 $d 21 (67,68) and even up to 7-12 g$d 21 to contribute to the preservation of muscle mass during stressors such as energy restriction (59). Leucine stimulation of anabolic pathways is decreased in the presence of sufficient essential amino acids (EAAs) (69), indicating an increased basal synthetic rate with adequate EAA ingestion, thus highlighting the importance of consuming dietary protein at levels above the current RDA during periods of energy deficit.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the requirement of several IAA such as lysine, leucine, methionine, and threonine have shown that their daily requirements in Indian adults are similar to those in Western populations (8,(14)(15)(16). Although it is likely that the same may apply to growing children, this is not known with any certainty.…”
Section: Introductionmentioning
confidence: 99%